PENGARUH LIKUIDITAS, SOLVABILITAS DAN AKTIVITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN MIRA-MAR BLOCK DILI TIMOR LESTE - de Jesus lay, Alexandre; Wiksuana, I.G.B. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.02.TAHUN 2018DO - 10.24843/EEB.2018.v07.i02.p10, 2018)
The aim of the study was to determine the effect of Liquidity, Solvency, and Activity on the profitability of the company of Mira Mar-Block Dili East Timor. The data used was obtained from the financial statements of the company of Mira-Mar Block, Dili, East Timor, in the form of Balance Sheet and Income Statement. After the data was collected then analyzed by using multiple linear regression analysis models. This analysis model used normality test, autocorrelation, multi co-linearity test, and permanent test of regression models. The Multiple Linear Regression analysis results showed that the Liquidity Ratio (CR) significantly effects on the Profitability (ROE), while the Solvency Ratio (DER) and the Ratio of Activity (TATO) do not significantly effect on the Profitability (ROE).